Patient satisfaction against the quality of dental health services at dental polyclinic of Tenriawaru General Hospital in Bone Regency - Fuad H. Akbar; Rini Pratiwi (Journal of Dentomaxillofacial Science, 2016)
Patient satisfaction against the quality of dental health serviceswas a comparison between the perception of care received by expectation before getting treatment. The Research was conducted at Tenriawaru General Hospital in Bone Regency based on the five dimensions of service quality, they were the assurance, empathy, responsiveness, physical appearance, and medical services by using Likert scale. The study was descriptive with a sample of 65 people. The research subjects were all visitors (patient) Dental Polyclinic of Tenriawaru General Hospital in Bone Regency. Results showed patient satisfaction on dimensions of assurance 84.6% falling into the category satisfied. On the dimensions of empathy showed 81.5% of patients satisfied. On the dimensions of responsiveness showed 36.9% of patients satisfied. On the dimensions of physical appearance showed 84.6% of patients satisfied. On the dimensions of medical services showed 72.3% of patients satisfied. Based on the result of patient satisfaction against the quality of dental health services at the Dental Polyclinic of Tenriawaru General Hospital in Bone Regency which reviewed from five dimensions showed patients satisfied against the quality of dental health services at Tenriawaru General Hospital in Bone Regency.